Sleep disorders in psoriasis - Julia Nowowiejska; Anna Baran; Iwona Flisiak (Termedia Publishing House, 2020)
Psoriasis is a chronic inflammatory skin disease affecting 2-4% of general population. Skin lesions may be accompanied by pruritus or pain, what may cause difficulties in daily functioning, and also disturb sleep. Many patients suffer from depression, which is often accompanied by sleep disorders, usually insomnia. Psoriasis is also strongly associated with metabolic syndrome and obesity, but also with obstructive sleep apnea syndrome. Research also shows that patients with psoriasis more frequently suffer from restless leg syndrome. Sleep disorders lead to significant deterioration of patients' quality of life, which is already decreased by the disease itself. Therefore, it is advisable to screen patients with psoriasis for sleep disorders, and introduce adequate treatment early during the course of the disease.